Chemical composition of Pacific manganese nodules and crusts analyzed at Scripps Institution of Oceanography using X-ray emission spectrometry - Yury P Girin; Viacheslav V Gordeev; Y G Gurvich; Vyacheslav N Lukashin; Areg A Migdisov; N V Barskaja (PANGAEA, 2023)
Manganese nodules, crusts and micronodules from dredges and cores were retrieved during campaign DM14 of R/V Dmitry Mendeleev in the Pacific Ocean. Their chemical composition was determined either by wet chemistry, atomic absorption spectroscopy or neutron activation depending upon the chemical element.